Effectiveness and safety of a one-yearly elongation approach of growing rods in the treatment of early-onset scoliosis: A case series of 40 patients with definitive fusion - Vittoria, Francesca; Ceconi, Viola; Fantina, Lisa; Barbi, Egidio; Carbone, Marco (Frontiers in Pediatrics, 2022)
Background: Early Onset Scoliosis (EOS) can lead to marked spine and chest wall deformity and often to profound cardiopulmonary compromise. Nowadays treatment benefits from the possibility of a growth friendly surgical approach, to avoid early spinal fusion. Growing rods spinal implants allow maximizing spine and thorax growth during childhood, performing lengthening procedures traditionally approximately every 6 months. Methods: We retrospectively evaluated 40 patients affected by EOS who underwent growing rods implantations from 2000 to 2020. A 1-year interval between lengthening procedures was adopted. Data about the age at first and final surgeries, T1-T12 length pre- and post-surgery, T1-S1 pre- and post-surgery, major coronal curve, pre- and post-surgery rate of complications and unplanned surgeries were collected and compared with those reported in the literature to determinate effectiveness and safety of this long period between distractions. Results: the lengthening procedures were performed, on average, every 12.3 months; children underwent an average of 4.6 lengthening procedures each. Major curve pre-first surgery was 78°, post-first surgery 45°, pre-final surgery 55°, and post-final surgery 43°. The mean absolute difference between pre-initial to post-final major curve was 35°, representing a mean relative difference of 42%. On average, the T1-T12 segment measured 15 cm before the first surgery and 24 cm after the final surgery, while the T1-S1 segment was 25 cm before the GR implantation and reached 37 cm after treatment. During treatment, the adverse events met affected 27 of the 40 total patients (67%) who experienced at least one complication. No differences were shown concerning both outcomes and complications, comparing these data with the available literature concerning most frequent elongations. This approach avoided four to five surgical procedures in this population. Conclusion: Our results related to deformity correction and complication rate are comparable with those found in the literature, where lengthening procedures are performed approximately every 6 months rather than with a 1-year interval between distractions. We also demonstrate a higher risk of complications for patients with implants before the age of 6.